2021
DOI: 10.3390/pr9061028
|View full text |Cite
|
Sign up to set email alerts
|

Process Intensification in Bio-Ethanol Production–Recent Developments in Membrane Separation

Abstract: Ethanol is considered as a renewable transport fuels and demand is expected to grow. In this work, trends related to bio-ethanol production are described using Thailand as an example. Developments on high-temperature fermentation and membrane technologies are also explained. This study focuses on the application of membranes in ethanol recovery after fermentation. A preliminary simulation was performed to compare different process configurations to concentrate 10 wt% ethanol to 99.5 wt% using membranes. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Employing ethanol-selective membranes instead of distillation is an option to concentrate bioethanol after fermentation that can reduce the energy required for the concentration [10]. For example, the permeate through hydrophobic inorganic membranes, such as silicalite membranes, can be over 85% when 10% ethanol solution is applied [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Employing ethanol-selective membranes instead of distillation is an option to concentrate bioethanol after fermentation that can reduce the energy required for the concentration [10]. For example, the permeate through hydrophobic inorganic membranes, such as silicalite membranes, can be over 85% when 10% ethanol solution is applied [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the permeate through hydrophobic inorganic membranes, such as silicalite membranes, can be over 85% when 10% ethanol solution is applied [11]. After an ethanol-selective membrane, a dehydration membrane can be applied to concentrate the ethanol further [10]. The separation properties of membranes are often evaluated by a pervaporation (PV) process, where a mixture liquid is supplied to the membrane and some fraction permeates through the membrane as a vapor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and concluded that the proposed system requires one-fourth of the energy required by distillation. Nevertheless, more research is required to develop RO membranes with such robustness (Kumakiri et al 2021).…”
Section: Membrane Processes 2171 Reverse Osmosismentioning
confidence: 99%
“…Among many membrane processes, pervaporation has been one of the most extensively studied for ethanol recovery from aqueous solutions and fermentation broth (Kumakiri et al 2021;Peng et al 2021;Vane 2008;Zentou et al 2019). It separates volatile compounds from the liquid feed by creating a difference in effective concentration between the feed and permeate.…”
Section: Pervaporationmentioning
confidence: 99%